Exploration of the mechanism of aloin ameliorates of combined allergic rhinitis and asthma syndrome based on network pharmacology and experimental validation - Feng, Yan; Qiao, Han; Liu, Hongyun; Wang, Jvfei; Tang, Huaping (Frontiers in Pharmacology, 2023)
Background: Aloin, as a bioactive compound, has a variety of pharmacological functions, but its effects on combined allergic rhinitis and asthma syndrome(CARAS)have not been studied. To clarify the protective effect and mechanism of aloin in the treatment of CARAS by network pharmacology, molecular dynamics simulation and experiment.Methods: The targets of aloin, allergic rhinitis and asthma were obtained from various databases.The protein interaction network was constructed for the common targets, and molecular docking and molecular dynamics simulations were performed for the core targets. Functional and pathway enrichment analysis of common targets was also performed using R software. varieties of biological experiments were conducted to verify the effect of aloin on the inflammatory changes of CARAS and its regulatory mechanism.Results: A total of 42 anti-allergic rhinitis and 58 anti-asthma targets were obtained, and 5 core anti-allergic rhinitis and 6 core anti-asthma targets were identified using topological analysis. GO and KEGG analyses showed that endopeptidase activity and MAPK signaling pathway played important roles in allergic rhinitis and asthma.Molecular docking and molecular dynamics simulations showed that aloin could stably bind to the core target proteins. Experimental verification showed that aloin significantly inhibited the expression of inflammatory factors, and may regulate CARAS by down-regulating MAPK signaling related proteins.Conclusion: This study identified the protective effect, potential target and mechanism 3 of aloin on CARAS. It provides reference for understanding the molecular mechanism and clinical application of aloin in the ameliorates of CARAS.